The Effect of Accounting Perception, Business Scale and Business Duration on the Preparation of MSME Financial Statements - Tiara Maulia; Puji Isyanto; Devi Astriani (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
This study aims to examine the effect of accounting perception, business scale, and business duration on the preparation of financial statements among MSMEs in Karawang Regency. A quantitative approach was employed through a survey of 100 MSME actors selected using random sampling. Data were collected via questionnaires and analyzed with SmartPLS 4. The results indicate that accounting perception, business scale, and business duration each have a positive and significant effect on MSME financial statement preparation. Business scale emerges as the most dominant predictor. These findings imply that the quality of financial reporting is shaped by business actors' awareness of accounting importance, operational complexity, and financial management experience. This study reinforces the application of the Theory of Planned Behavior in explaining MSME financial reporting behavior.